1470. Neurocognitively-Acting Potentially Inappropriate Medications, Alcohol, and Community-Acquired Pneumonia Among Patients with and Without HIV. (26th November 2018) - Rentsch, Christopher T; Tate, Janet P; Gordon, Kirsha S; Tseng, Alice; Niehoff, Kristina M; Crothers, Kristina A; Edelman, E Jennifer; Justice, Amy C; ,
Abstract: Background: Alcohol interactions with neurocognitively-acting potentially inappropriate medications (NC-PIMs) may be more common, more harmful, and associated with lower levels of alcohol use among people living with HIV. Methods: We conducted a nested case–control study using data from the Veterans Aging Cohort Study (2007–2015). Cases with community-acquired pneumonia (CAP) requiring hospitalization ( n = 6, 716) were 1:5 matched to controls without CAP ( n = 33, 253) at the time of event by age, sex, race, HIV status, baseline year, and duration of observation time. Index date was defined as CAP date for cases and match date for controls. Based on pharmacy data in the year prior to index date, NC-PIMs included receipt of at least one prescription of any duration for anticonvulsants, sedatives (including benzodiazepines), prescription opioids, antidepressants, antipsychotics, and muscle relaxants. Among HIV+, NC-PIMs exposure also included ritonavir (RTV), cobicistat (COBI), and efavirenz (EFV). Conditional logistic regression models were used to obtain adjusted odds ratios (OR) and 95% confidence intervals (CI) for NC-PIMs (any and count overall, and by class), alcohol use disorder (AUD) diagnoses in the year prior to index date, and their interaction adjusted for smoking status, VACS Index, steroids, vaccination status (influenza and pneumonia), hepatitis C, previous CAP, and various comorbidities. Results: Among 39, 989 patients, 17, 161 (43%) were HIV+, 98% were male, and median age was 58 years. An increase in number of classes of NC-PIMs was associated with a 17% increase in the odds of CAP among HIV+ and uninfected, and this effect was augmented by contemporaneous AUD. Among HIV+, all classes of NC-PIMs apart from EFV were positively associated with CAP, most notably antipsychotics (OR 1.66, 95% CI 1.43–1.93). Among uninfected, the highest risk of CAP was associated with antipsychotics (OR 1.81, 95% CI 1.61–2.03) and anticonvulsants (OR 1.64, 95% CI 1.49–1.80). AUD positively interacted with sedatives, opioids, antidepressants, and muscle relaxants in both groups, and with RTV/COBI in HIV+ patients. Conclusion: NC-PIMs, especially with concurrent AUD, are associated with increased CAP risk among those living with and without HIV. Disclosures: All authors: No reported disclosures.